“Go Healthy”: Diet Catering for Obese Consumers with a Consumer Discovery Approach - Putri, Nadya Yona Eka; Retnaningsih, Retnaningsih; Taryana, Asep (Journal of Consumer Sciences, 2023)
The main health problem in the adult age group in Indonesia is obesity, which is closely related to diet. The purpose of this research is to design a verified business model for "Go Healthy" catering. This research uses a consumer discovery approach and a descriptive research design. Data collection was carried out by purposive sampling in the Jabodetabek area. The research respondents were 50 people aged 19-24 years who were interested in diet programs. Data were collected by filling out online questionnaires and in-depth interviews. Based on the results of the research, the problems found in this study are irregular diets, poor food quality, and nutritional deficits. These problems became the basis for the formation of the "Go Healthy" catering prototype. The "Go Healthy" catering prototype is a menu arrangement for 15 days with the value offered including menu customization, menu composition info with nutritional content, and affordable prices. The business is ffered through online and offline outlet channels and through resellers. The business revenue comes from a subscription system.